2021
DOI: 10.12688/wellcomeopenres.16336.2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease risk and pathophysiology in South Asians: can longitudinal multi-omics shed light?

Abstract: Cardiovascular disease (CVD) is the leading cause of mortality in South Asia, with rapidly increasing prevalence of hypertension, type 2 diabetes (T2DM) and hyperlipidemia over the last two decades. Atherosclerotic CVD (ASCVD) affects South Asians earlier in life and at lower body weights, which is not fully explained by differential burden of conventional risk factors. Heart failure (HF) is a complex clinical syndrome of heterogeneous structural phenotypes including two major clinical subtypes, HF with preser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 130 publications
(122 reference statements)
0
7
0
Order By: Relevance
“…A recent study integrated proteomic and transcriptomics from immune cells identified activated T-cells and macrophages in atherosclerotic plaques and a greater proportion of exhausted T-cells in symptomatic patients though further research is needed to establish whether exhaustion occurs before or after the cardiovascular event [145]. Longitudinal study designs in multi-omics can aid in resolving the order of molecular events [146], and they have recently been used to resolve the temporal fate of immune cell states during the course of COVID-19 and discover inflammatory signatures preceding fatal outcomes [147,148]. Longitudinal sampling can also identify patterns within and between 'omics layers that vary over time.…”
Section: Future Directions In the Fieldmentioning
confidence: 99%
“…A recent study integrated proteomic and transcriptomics from immune cells identified activated T-cells and macrophages in atherosclerotic plaques and a greater proportion of exhausted T-cells in symptomatic patients though further research is needed to establish whether exhaustion occurs before or after the cardiovascular event [145]. Longitudinal study designs in multi-omics can aid in resolving the order of molecular events [146], and they have recently been used to resolve the temporal fate of immune cell states during the course of COVID-19 and discover inflammatory signatures preceding fatal outcomes [147,148]. Longitudinal sampling can also identify patterns within and between 'omics layers that vary over time.…”
Section: Future Directions In the Fieldmentioning
confidence: 99%
“…The environmental exposures can modify the gene expression levels through epigenetic mechanisms, and this modification can be inherited across cell generations to exert a long-term impact on the development of CVD. 5 Atherogenesis is a prolonged multistep process that involves endothelial dysfunction and lipoprotein retention on the arterial walls, followed by lymphocyte infiltration, inflammation, foam cell formation, plaque buildup and thrombosis. The fibrous cap which forms around the plaque acts as a protective barrier between the prothrombic atheroma and the platelets in the bloodstream.…”
Section: Abdul Jaleelmentioning
confidence: 99%
“…Pattern : Heart attack, coronary heart disease, stroke, and kidney disease CVD includes a number of cardiac conditions including (a) coronary heart disease, either angina or heart attack, (b) stroke, which is caused by a blockage of a blood clot (known as ischemic stroke) or the rupture of a blood vessel and bleeding (known as hemorrhagic stroke), and (c) peripheral vascular disease which refers to the obstruction of the large blood vessels that supply blood to the arms and legs (51).…”
Section: Pattern : Arthritis Asthma Respiratory Diseases and Depressionmentioning
confidence: 99%